2024
DOI: 10.3390/buildings14020482
|View full text |Cite
|
Sign up to set email alerts
|

Research Perspectives on Buildings’ Sustainability after COVID-19: Literature Review and Analysis of Changes

Ugo Maria Coraglia,
Davide Simeone,
Marco Alvise Bragadin

Abstract: The concept of sustainability introduced in 1987 has characterised the world of research in the AEC (Architecture, Engineering, and Construction) sector, directing it to try to tackle the problems inherent to the impacts of climate change on buildings. In addition, the advent of COVID-19, disrupting the world and people’s habits, has obviously also strongly affected the academic world. Indeed, this paper aims to analyse the changes and differences between the pre- and post-pandemic periods through a two-stage … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 96 publications
0
1
0
Order By: Relevance
“…The above has revealed that, in recent years there has been a notable increase in the number of studies analysing the impact of the pandemic and its consequences on society and the environment [28][29][30][31][32]. Key topics have been the lockdown's effect on the environment, changes in product demand, plastic usage, and the subsequent increase in waste.…”
Section: Covid-19 and Environmental Efficiency In The Hospital Sectormentioning
confidence: 99%
“…The above has revealed that, in recent years there has been a notable increase in the number of studies analysing the impact of the pandemic and its consequences on society and the environment [28][29][30][31][32]. Key topics have been the lockdown's effect on the environment, changes in product demand, plastic usage, and the subsequent increase in waste.…”
Section: Covid-19 and Environmental Efficiency In The Hospital Sectormentioning
confidence: 99%